La heterogeneidad de la imagen de China en la política exterior latinoamericana. Perspectivas para la concertación de políticas (Tema Central) - Bernal-Meza, Raúl (2014)
The text shows the heterogeneous views of various Latin American countries, like Mexico, Brazil, Argentina, Chile, Colombia and Venezuela, in terms of their analyses of and studies about foreign policy. This paper aims to make clear the different images that China generates as a rising power in the world economy, particularly as a major trade partner of these countries. The goal of this article is to provide elements for analysis about policy coordination vis-àvis China. The central argument states that there should be coordination between regional integration strategies and foreign policies in relation to China. However, these heterogeneous visions can work against that goal as well.